Lung Cancer Heterogeneity in Modulation of Th17/IL17A Responses - Armstrong, Dominique; Chang, Cheng-Yen; Lazarus, Donald R.; Corry, David; Kheradmand, Farrah (Frontiers in Oncology, 2019)
The interplay between tumors and their immune microenvironment is critical for cancer development and progression. The discovery of tumor heterogeneity has provided a window into a complex interplay between tumors, their secreted products, and host immune responses at the cellular and molecular levels. Tumor heterogeneity can also act as a driving force in promoting treatment resistance and correlates with distinct tumor-mediated acquired immune responses. A prevailing question is how genetic aberrations in solid tumors can shape the immune landscape, resulting in pro-tumor or anti-tumor activities. Here we review evidence for clinical and pathophysiological mechanisms that underlie different types of non-small cell lung cancer (NSCLC) and provide new insights for future immunomodulatory-based therapies. Some of the more common driver mutations in NSCLC heterogeneity includes the opposing immune responses in oncogenic mutations in K-ras vs. non-K-ras models and their pro-inflammatory cytokines such as interleukin (IL)-17A. We will discuss possible molecular and metabolic mechanisms that may govern the opposing immune responses observed in distinct genetic models of NSCLCs. A deeper understanding of how tumor heterogeneity modulates immune response can improve current therapeutic strategies and provide precise treatment to individual lung cancer patients.